Heterodimer of HER2/HER3 receptors, autocrine heregulins and cyclo-oxygenase 2, and Herceptin effects - Szacikowska, Ewa; Kozłowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2000)
Three oncoproteins are presented in this work. They are responsible for disturbance of normal cellular growth, leading to neoplastic transformation and progression of malignant phenotype in the case of epithelial neoplasms with HER2 (p185) receptor overexpression. In this context, therapeutically favourable, more multidirectional Herceptin effect is presented. On the basis of review of world literature on this problem, covering recent five years of basic and clinical studies it was demonstrated that the development and progression of malignant phenotype of epithelial tumours with p185 receptor overexpression is founded on three-point axis established by the effects of three oncoproteins, mutually regulating themselves: HER2 and HER3 receptor heterodimer, autocrine heregulins and cyclo-oxygenase2 (cox2). The central link of this axis is heterodimer of HER2 and HER3 receptors. The blockade of this link with Herceptin neutralizes the mitogenic activity of the remaining two oncoproteins since they transmit their stimulations either as autocrine heregulins via this special heterodimer, or as in the case of cyclo-oxygenase2, the heterodimer induces oncogenic, constitutional activation of COX2 gene with all cancerogenic results of this enzyme’s action.